IMPLEMENTATION OF THE POLICY PROHIBITING THE KILLING OF ESTUARY CROCODILES IN RANTAU GEDANG AND TELUK RUMBIA VILLAGES, SINGKIL DISTRICT, ACEH SINGKIL REGENCY - Fitrianda Sari; Mauludi; Arinanda; Muhammad Hasyem; Risna Dewi (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study examines the implementation of the policy prohibiting the killing of estuarine crocodiles in Rantau Gedang Village and Teluk Rumbia Village, Singkil District, Aceh Singkil Regency, as well as the factors hindering its implementation. The study was motivated by increasing human–crocodile conflicts that have resulted in fatalities and created a dilemma between wildlife conservation and community safety. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The analysis is based on Merilee S. Grindle's policy implementation theory, which focuses on policy content and implementation context. The findings indicate that the prohibition policy has not been implemented optimally. Although it has a strong legal foundation and clear objectives, it has not fully addressed the community's need for safety. The main barriers include low community compliance, limited resources, inadequate continuous socialization, weak inter-agency coordination, and the socio-economic dependence of local communities on river activities. A more comprehensive strategy is therefore required through improved public awareness, strengthened monitoring, and human–wildlife conflict mitigation so that estuarine crocodile conservation can be balanced with community safety and welfare.